Efektivitas Teknik Kimia Kata untuk Meningkatkan Keterampilan Menulis Puisi Siswa Kelas VIII SMP Negeri 3 Maos Tahun 2025 - Vani Indra Pramudianto; Eko Suroso (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to evaluate the effectiveness of the “Word Chemistry” technique in improving poetry writing skills of 8th-grade students at SMP Negeri 3 Maos during the 2024/2025 academic year. The background of this research lies in students’ limited ability to choose precise diction and express strong imagination in writing poetry. “Word Chemistry” is a creative technique that encourages imaginative exploration and combination of words, similar to chemical reactions, enriching students’ vocabulary and poetic expression. A quasi-experimental method was applied using a pretest-posttest design involving two groups: experimental and control. The primary instruments included poetry writing tests and scoring sheets assessing diction, imagery, creativity, and expression. Data analysis revealed a significant difference between pretest and posttest scores in the experimental group (p = 0.00000122), with 90.63% of students showing improvement, although most gains were categorized as low to moderate based on N-Gain analysis. The study concludes that the Word Chemistry technique significantly enhances students’ poetry writing skills and holds promise as a creative and enjoyable method for teaching literary expression.